2005
DOI: 10.1088/0953-8984/17/27/r01
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-doped TiO2and ZnO—present status of the field

Abstract: There has been considerable recent interest in the design of diluted magnetic semiconductors, with a particular focus on the exploration of different semiconductor hosts. Among these, the oxide-based diluted magnetic semiconductors are attracting increasing attention, following reports of room temperature ferromagnetism in anatase TiO 2 and wurtzite ZnO doped with a range of transition metal ions. In this review we summarize the current status of oxide-based diluted magnetic semiconductors, and discuss the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
325
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(350 citation statements)
references
References 163 publications
10
325
1
5
Order By: Relevance
“…These exhibit large MCD without an appearance of ferromagnetism, although several studies reported high-T C ferromagnetism in the same compound. 5,6 X-ray diffraction experiments were performed using four-circle diffractometers installed at beamlines 1A, 4C, and 16A2 of the Photon Factory in KEK, Japan. The incident beam was monochromatized by a Si-111 double crystals and focused by a bent cylindrical mirror.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These exhibit large MCD without an appearance of ferromagnetism, although several studies reported high-T C ferromagnetism in the same compound. 5,6 X-ray diffraction experiments were performed using four-circle diffractometers installed at beamlines 1A, 4C, and 16A2 of the Photon Factory in KEK, Japan. The incident beam was monochromatized by a Si-111 double crystals and focused by a bent cylindrical mirror.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Since the discovery of room temperature ferromagnetism in Codoped anatase and rutile TiO 2 thin film, 3,4 there have been a number of reports on high-T C ferromagnetism observed in various kinds of DMS, particularly in oxides. 5,6 Co-doped TiO 2 is the material that has been studied most intensively. However, the origin of the ferromagnetism has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, a variety of these transition-metals have been explored as dopants in modifying the electronic structure of TiO 2 to improve its visiblelight photocatalytic activity. [25][26][27][28] Because of the interaction between t 2g state of TM-dopants and Ti atoms, transitionmetal doping could considerably create an additionally oc- Figure S5) exhibit a variety of colors, departing from the white color of the undoped product. For instance, Rh-doped samples show a deep brown color resulted from the strong absorption in visible region (Figure 2).…”
mentioning
confidence: 99%
“…
Recently, it was found that the ZnO, TiO 2 , Cu 2 O and SnO 2 oxide semiconductors, doped by 3Delements can be ferromagnetic with the Curie temperature significantly above room temperature when the magnetic ions concentration is significantly lower than the percollation threshold [1][2][3]. As a rule these compounds are prepared in the form of nanocrystals by means of substantially nonequilibrium technique with large number of defects (for example, the vacancies in anion (oxygen) or cation sublattice as well as surface defects).
…”
mentioning
confidence: 99%